ANALYSIS OF CURRICULUM MANAGEMENT ON STUDENT LEARNING OUTCOMES - Syamsidah Lubis Syamsidah; Saidah Oktariyati; M. Siddik; Enik Nur Faiza; Alya Rahmadhani (Leadership:Jurnal Mahasiswa Manajemen Pendidikan Islam, 2026)
The aims study to analyze the influence of curriculum management on student learning outcomes at SMP Mashita Batam. Curriculum management in this study encompasses aspects of planning, organizing, implementing, and evaluating learning at the school. This think about utilized a quantitative approach with clear explanatory strategies. Information collection was conducted through surveys and documentation. The information gotten were at that point analyzed utilizing prerequisite tests (ordinariness and linearity tests), taken after by straightforward straight relapse and coefficient of assurance tests utilizing SPSS. The comes about appeared that the information were regularly disseminated and had a straight relationship. Based on the relapse test, a centrality esteem of 0.002 (<0.05) was gotten, hence concluding that there's a noteworthy impact between educational modules administration and understudy learning results. Subsequently, it can be concluded that curriculum administration encompasses a critical impact on understudy learning results at SMP Mashita Batam, although the level of impact is generally moo. In this manner, nonstop advancement within the quality of educational programs administration usage is required to back the accomplishment of more ideal learning results. Keywords Keywords: Analysis, Curriculum Management, Students Learning Outcomes   Abstrak Studi berikut bertujuan guna mengevaluasi dampak manajemen kurikulum pada pencapaian belajar siswa di SMP Mashita Batam. Dalam studi berikut, manajemen kurikulum meliputi berbagai aspek seperti pengorganisasian, perencanaan, pelaksanaan, serta evaluasi pembelajaran yang dijalankan di sekolah. Studi berikut mengambil pendekatan kuantitatif melalui metode analisis deskriptif. Penghimpunan data dijalankan lewat kuesioner dan dokumentasi. Data yang dikumpulkan selanjutnya dianalisis dengan uji normalitas dan linearitas, diikuti pada uji regresi linear sederhana serta uji koefisien determinasi dengan mempergunakan program SPSS. Temuan pada studi berikut memperlihatkan bahwasanya data memiliki distribusi normal dan terdapat korelasi yang linier. Dari hasil analisis regresi, didapatkan skor signifikansi senilai 0,002 (lebih kecil dari 0,05), dengan begitu bisa ditarik simpulan bahwasanya manajemen kurikulum mempengaruhi hasil belajar siswa secara signifikan. Sehingga, kesimpulannya ialah manajemen kurikulum berdampak signifikan pada hasil belajar siswa di SMP Mashita Batam, meski dampaknya terbilang rendah. Maka sebab itu, dibutuhkan peningkatan kualitas pelaksanaan manajemen kurikulum yang berkesinambungan untuk menunjang capaian hasil belajar yang maksimal. Kata Kunci: Analisis, Hasil belajar Siswa, Manajemen Kurikulum